2004
DOI: 10.1016/j.micpath.2003.10.001
|View full text |Cite
|
Sign up to set email alerts
|

High growing ability of Vibrio vulnificus biotype 1 is essential for production of a toxic metalloprotease causing systemic diseases in humans

Abstract: Vibrio vulnificus biotype 1, a causative agent of fatal septicemia or wound infection in humans, is known to produce a toxic metalloprotease as an important virulence determinant. V. vulnificus biotype 2 (serovar E), a primary eel pathogen, was found to elaborate an extracellular metalloprotease that was indistinguishable from that of biotype 1. The potential of V. vulnificus biotype 1 for production of the metalloprotease was compared with biotype 2 and other human non-pathogenic Vibrio species (V. anguillaru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 41 publications
2
27
0
1
Order By: Relevance
“…Shinoda and co-workers recently reported that a high growth rate of V. vulnificus in conditions with an abundance of available iron is essential for the efficient production of proteases. 38,39) These results indicate that iron is required for efficient VvpE production, and that VvpE is not required for efficient iron-uptake. However, controversy remains between VvpE production and iron concentration.…”
Section: Discussionmentioning
confidence: 91%
“…Shinoda and co-workers recently reported that a high growth rate of V. vulnificus in conditions with an abundance of available iron is essential for the efficient production of proteases. 38,39) These results indicate that iron is required for efficient VvpE production, and that VvpE is not required for efficient iron-uptake. However, controversy remains between VvpE production and iron concentration.…”
Section: Discussionmentioning
confidence: 91%
“…Iron seems to enhance the virulence of vibrios. A capsular polysaccharide (CPS) is the primary virulence factor in V. vulnificus pathogenesis (270,422,441). The presence of this factor correlates with the opaque colony phenotype and is thought to play a inflammatory role within the human body.…”
Section: Human Pathogensmentioning
confidence: 99%
“…Bioremediation of polyaromatic hydrocarbons may be carried out by vibrios (161). Vibrios may also be 422 THOMPSON ET AL. MICROBIOL.…”
Section: Perspectives and Exploitationmentioning
confidence: 99%
“…This means that they are likely to be substrates for protease enzymes that are found in tissue. In particular, extracellular proteases derived from the host cells are found in areas of inflammation such as infections (1,23) and proteases may also be produced by bacteria them-selves as secreted virulence factors involved in tissue invasion (30,47).…”
Section: Vol 50 2006 Photoinactivation With Pei-chlorin(e6) Conjugamentioning
confidence: 99%